1992
DOI: 10.1002/j.1556-6978.1992.tb00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Counselors and Exceptional Students: Preparation Versus Practice

Abstract: Despite the multiple roles of school counselors related to special education, a national survey of counselor education programs indicated that most programs encourage, but do not require, training to work with exceptional students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 8 publications
1
25
0
Order By: Relevance
“…Despite the apparent need for school counselors to work closely with ES, the results of this survey were similar to previous research findings (Korinek & Prillaman, 1992), which reported that the majority of school counselor preparation programs did not have specific course requirements in ESE. Despite the lack of ESE course work.…”
Section: Discussionsupporting
confidence: 88%
“…Despite the apparent need for school counselors to work closely with ES, the results of this survey were similar to previous research findings (Korinek & Prillaman, 1992), which reported that the majority of school counselor preparation programs did not have specific course requirements in ESE. Despite the lack of ESE course work.…”
Section: Discussionsupporting
confidence: 88%
“…This adds another dimension to the complexity of adequately training and supervising school psychologists in a university setting. However, forging partnerships with community agencies has been a viable option for diversifying practicum and internship experiences (Adelman, 1996;Korinek & Prillaman, 1992). University programs must also consider working more closely with local school district crisis teams to provide school-based experiences related to crisis intervention.…”
Section: Discussionmentioning
confidence: 98%
“…Suggestions for aligning university academic training for crisis intervention with the current demands placed on practitioners in the schools include: (a) increasing academic exposure to topics related to crisis intervention and prevention, particularly for suicide, violence/aggression, and creating school district crisis plans; (b) providing opportunities for experiences related to crisis intervention during practicum and internship; and (c) providing quality supervision of practicum and internship experiences related to crisis intervention (Korinek & Prillaman, 1992).…”
Section: Discussionmentioning
confidence: 98%
“…In assuming team leadership, counselors are encouraged to draw on knowledge, skills, and attitudes that support and foster a collaborative team process including frequent communication and coordinated efforts Keys, Bemak, Carpenter, & King-Sears, 1998). Although collaboration concerning children with disabilities is typically required of school counselors, most school counseling training programs do not include training in how to work specifically with these children, their families, or related school personnel (Frantz & Prillaman, 1993;Korinek & Prillaman, 1992;Milsom, 2002). Thus, as noted in the general teaching literature, school counselors also report feeling unprepared to work with students with disabilities (Milsom, 2002).…”
mentioning
confidence: 98%
“…Traditionally, the school counselor's primary role has been to provide support and service to students in general education (Tarver-Behring & Spagna, 1998); however, increasingly the counselor is called on to support all students, including those with disabilities (ASCA, 2004a; Korinek & Prillaman, 1992;Milsom, 2002;Tarver-Behring & Spagna, 1998). Counselors are encouraged to take a leadership position in implementing a collaborative process to enhance student support and outcomes (Bemak & Cornely, 2002;Musheno & Talbert, 2002).…”
mentioning
confidence: 98%